Polarizzazioni antinomiche su IA e digitale: il ruolo della pedagogia - Gennaro Balzano (Studi sulla Formazione)
In an era marked by the pervasiveness of Artificial Intelligence and the emergence of digital life forms increasingly integrated into human everyday life, this contribution aims to outline a pedagogical phenomenology of being onlife. Starting from a critical-hermeneutic stance, the present reflection advocates the abandonment of an antinomic paradigm – one inherently shaped by the logic of opposition, the versus – in favor of an educational framework conceived to enact a maieutic and generative role.